Insulin Degludec Requires Lower Bolus Insulin Doses Than Does Insulin Glargine in Japanese Diabetic Patients With Insulin-Dependent State - Komuro, Manaho (J Diabetes Sci Technol, 2014)
Background: The study presents a comparison of the glucose-lowering effects, glycemic variability, and insulin doses during treatment with insulin degludec or insulin glargine. Methods: In this open-label, single-center, 2-way crossover study, 13 Japanese diabetic outpatients in the insulin-dependent state on basal-bolus therapy were assigned to receive either insulin glargine followed by insulin degludec, or insulin degludec followed by insulin glargine. Basal insulin doses were fixed in principle, and patients self-adjusted their bolus insulin doses. Seventy-two-hour continuous glucose monitoring was performed 2 weeks after switching the basal insulin. Results: Mean blood glucose (mg/dL) was not significantly different between insulin degludec and insulin glargine over 48 hours (141.8 ± 35.2 vs 151.8 ± 43.3), at nighttime (125.6 ± 40.0 vs 124.7 ± 50.4), or at daytime (149.3 ± 37.1 vs 163.3 ± 44.5). The standard deviation (mg/dL) was also similar (for 48 hours: 48.9 ± 19.4 vs 50.3 ± 17.3; nighttime: 18.7 ± 14.3 vs 13.7 ± 6.7; daytime: 49.3 ± 20.0 vs 44.3 ± 17.7). Other indices of glycemic control, glycemic variability, and hypoglycemia were similar for both insulin analogs. Total daily insulin dose (TDD) and total daily bolus insulin dose (TDBD) were significantly lower with insulin degludec than with insulin glargine (TDD: 0.42 ± 0.20 vs 0.46 ± 0.22 U/kg/day, P = .028; TDBD: 0.27 ± 0.13 vs 0.30 ± 0.14 U/kg/day, P = .036). Conclusions: Insulin degludec and insulin glargine provided effective and stable glycemic control. Insulin degludec required lower TDD and TDBD in this population of patients.